Recently Graduated Midwives in Uganda: Self-perceived Achievement, Wellbeing and Work Prospects - Copestake, James; Theuss, Marc; Davies, Gabby; Mukuru, Moses; Kyakuwaire, Hellen; Edwards, Grace (Midwifery, 2020)
To investigate how recent graduates from a combined work/study midwifery degree programme in Uganda viewed its effects on their wellbeing and work prospects. Using an adapted version of the Qualitative Impact Protocol (QuIP), a phenomenological approach was applied to thematic analysis to examine semi-structured interviews and WhatsApp group discussion. Introduction of enhanced midwifery training (from Diploma to Degree level) combining study with professional practice within a low income country health system facing extreme capacity constraints.
Keywords: Stress management; Midwifery; Midwifery education